OPTIMIZING AUDIT QUALITY THROUGH THE ROLE OF E-AUDIT, AUDIT FEES, AND TIME BUDGET PRESSURE IN PUBLIC ACCOUNTING FIRMS - Syabitha, Fidya Nur; Anggraini, Leriza Desitama; Hendarmin, Rum (JEA17: Jurnal Ekonomi Akuntansi, 2025)
The advancement of technology in the auditing field has driven Public Accounting Firms (KAP) to adopt e-audit to enhance efficiency and accuracy in the audit process. Additionally, audit fees and time budget pressure are considered factors that may influence audit quality. However, the extent to which these factors impact audit quality remains a topic of debate. Therefore, this study aims to analyze the effect of e-audit, audit fees, and time budget pressure on audit quality in Public Accounting Firms. This study employs a quantitative method with data collected through questionnaires distributed to auditors in various Public Accounting Firms. The sample was selected using purposive sampling from 100 respondents, with criteria set by the author based on audit practice. The data was analyzed using Structural Equation Modeling (SEM) with SmartPLS version 4 to comprehensively examine the relationships between variables. The findings indicate that e-audit and time budget pressure have a positive and significant impact on audit quality, while audit fees do not have a significant effect. These results suggest that implementing audit technology enhances auditors' effectiveness, while well-managed time pressure improves productivity without compromising audit quality. Based on these findings, Public Accounting Firms are advised to optimize the use of e-audit and implement better time management strategies to maintain audit quality in dynamic work conditions